UJI EFEKTIVITAS KRIM BUNGA KAMBOJA (PLUMERIA SP.) DALAM PENYEMBUHAN ULKUS KAKI DIABETIKUS - Suhartanto, Klarissa; Yusuf, Anggleri Julia; Prijadi, Evelyn Andreana (Essence of Scientific Medical Journal; Vol 20 No 1 (2022): Volume 20 No. 1 (Januari - Juli 2022) Essential: Essence of Scientific Medical Journal, 2022)
Introduction : Diabetes mellitus is a disease with a high number of cases. Complication of diabetes mellitus, such as diabetic foot ulcer, is rarely discussed. Treatment of diabetic foot ulcers often become a burden due to high cost, so a breakthrough is needed. Flavonoids have been reported to have benefits on wound healing. One of the plants that contain flavonoids is frangipani flower (Plumeria sp.). Methods : The cream made in 3 concentrations : 25%, 50%, and 75%. Cream was given to 24 rats that had been induced with alloxan. The cream will be given 2 times a day and the wound area is observed for 7 days. The rats will be euthanized and histological observations are made by hematoxylin preparations for collagen that will be analysis by ImageJ. Results : Wound closure and collagen area of the treated group better than the control group. The average wound closure of group I was 37.25%, group II was 75.75%, group III was 66.67%, and group IV was 61.70%. The average area of collagen in group I is 265776 pixels2, group II is 399579.5 pixels2, group III is 281749.75 pixels2, and group IV is 271382.9 pixels2. Discussion : The best result is group II. Increasing the dose of the cream didn’t give more significant effect so 25% dose was the maximum effective dose (MaxED). Conclusion : The administration of frangipani flower extract cream (Plumeria sp.) effective for diabetic foot ulcers and the maximum effective dose was 25%. Keywords : frangipani flower, diabetic foot ulcers, collagen, flavonoids